Comparison of Online Prescription Services Between Good Doctor and Halodoc at Nizam Farma Pharmacy - Intan Permata Sari; Lusiana Ariani; Nazwa Aulia Rusli; Rasta Naya Pratita (Faculty of Pharmacy Universitas Pancasila, 2026)
Pharmaceutical services play a pivotal role in healthcare delivery and have increasingly evolved through the integration of digital technologies, particularly online prescription services. This study compared the characteristics of online prescription services provided through Good Doctor and Halodoc at Nizam Farma Pharmacy between January and March 2025. A quantitative descriptive study was conducted using archived electronic prescription records obtained from both platforms. The data were analyzed based on prescription volume, physician specialty, medication categories, and medication access outcomes. The results indicated that Halodoc generated the highest proportion of prescriptions (61.6%), predominantly issued by general practitioners (76.5%), with symptomatic medications and antibiotics representing the most frequently prescribed drug categories. Conversely, prescriptions received through Good Doctor were primarily issued by specialist physicians (73.6%) and were largely intended for the management of mild conditions, including allergic disorders and upper respiratory tract illnesses. Overall, the findings indicate that online prescription platforms have the potential to improve medication access and support pharmaceutical services in community pharmacy practice.